Nail lesions in palmoplantar pustulosis and pustulotic arthro-osteitis impairs patients' quality of life: Suggesting new assessment tool of PPP nail lesions. Issue 1 (April 2022) - Masuda-Kuroki, Kana; Kawakami, Hiroshi; Abe, Namiko; Mori, Miho; Tobita, Rie; Fukushi, Ruri; Hiruma, Junichiro; Takeda, Yoshiki; Okubo, Yukari
Abstract: Background: Palmoplantar pustulosis (PPP) sometimes presents with nail lesions, which affect the patients' quality of life (QOL). However, little is known about nail lesions in PPP, and there is currently no established method for assessing them. Objective: This study aimed to analyze the impact of PPP-related nail lesions with the patients' QOL. In addition, we considered whether they might constitute a risk factor of pustulotic arthro-osteitis (PAO).' Methods: A total of 178 patients with PPP were enrolled. Among the 178 patients, 66 patients participated in the following quality of life questionnaires; GHQ28, DLQI, and Skindex-16. The severity of the nail lesions was classified according to the Nail Psoriasis Severity Index (NAPSI), and the types of nail lesion were investigated. Results: The DLQI, Skindex-16 and PPPASI scores were significantly higher in patients with nail lesions than in those without them. Indentions, transverse ridging, and nail thickening were relatively common in PPP. Nail lesions were unrelated to the presence of PAO complications, but leukonychia and discoloration were likely to be related to PAO lesion site. Conclusions: The study demonstrated that the presence of nail lesions is associated with a decreased QOL regardless of the severity of the skin lesions. The nail lesions were not a risk factor of PAO, but a predictor of skin lesion severity and PAO lesion site. Given this association, indention, transverse ridging, and thickening of the nail, currently not included in the NAPSI, should be added as an assessment item in the evaluation of PPP nail lesions. Highlights: Nail lesions are affected by the severity of skin conditions. The QOL is related to the presence of nail lesions of palmoplantar pustulosis. In the absence of nail lesions, the QOL is related to skin lesion severity. Nail lesions are unlikely to be a risk factor of pustulotic arthro-osteitis. Nail lesions may impair QOL of palmoplantar pustulosis.